Wage dispersion and workers' effort - Maria Fernanda Rivas; Matthias Sutter (University of Innsbruck, Department of Public Finance, 2008)
We study experimentally the relationship between intra-firm wage dispersion chosen by principals and workers' performance. Principals show a preference for more egalitarian wage schemes, and workers are negatively influenced by high levels of wage inequality.
Keywords: C92; J33; M52; 330; wage dispersion; effort; experiment; gift-exchange; Lohnstruktur; Vergütungssystem; Leistungsmotivation; Test